KEKSALARDA KUZATILADIGAN DEPRESSIYA YOLG’IZLIKNING OMILI SIFATIDA - Rustamova, T.N. (SCIENCE and SOCIETY, 2021)
This article provides information on the socio-psychological characteristics of loneliness and loneliness-related depression in old age and the factors that contribute to depression.
Keywords: gerontology; needs; stress; depression; phobia; Alzheimer's illness; progressive